The conscience of a liberal - Krugman, Paul R. (W.W. Norton & Co., 2007)
Today's most widely read economist challenges America to reclaim the values that made it great. Here he studies the past eighty years of American history, from the reforms that tamed the harsh inequality of the Gilded Age to the unraveling of that achievement and the reemergence of immense economic and political inequality since the 1970s. Seeking to understand both what happened to middle-class America and what it will take to achieve a "new New Deal," Krugman has woven together a nuanced account of three generations of history with sharp political, social, and economic analysis. This book, written with Krugman's trademark ability to explain complex issues simply, may transform the debate about American social policy.--From publisher description.